Relationship between obesity and thyroid function in adults - UZUNER, ARZU (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: Obesity affects prognosis of many comorbid diseases negatively. This study was conducted to investigate the relationship between obesity and thyroid function. Materials and Methods: This cross-sectional study was conducted between December 2011 and December 2012. Consecutively selected adults who applied to the outpatient clinics of Family Medicine and Internal Medicine, at Marmara University Hospital were recruited in the study. Height and weight were measured and body mass index (BMI) was calculated. Thyroid-stimulating hormone (TSH), free thyroxine (fT4), total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride and glucose levels were measured for every participant. According to their BMI, participants were divided into three groups as normal weight (< 25), overweight (25-30) and obese (>= 30). Results: Data of 618 participants (53% female/47% male) was analyzed. Mean age was 43 +/- 15. There were 175 (28.3%) participants in normal weight, 242 (39.2%) in overweight and 201 (32.5%) in obese groups. No statistically significant difference was found between groups in terms of TSH or fT4. Statistically significant difference was found in terms of lipid profiles and blood glucose between groups. Atherogenic lipid levels (total cholesterol, LDL and triglyceride) and blood glucose were higher and HLD levels were lower in overweight or obese groups P<0.05) but there were no statistically significant differences between overweight and obese groups (P>0.05). Conclusion: This study is one of the few studies in the literature showing that there is no relationship between obesity and thyroid function.
Keywords: Obesity; Adults; Thyroid function tests; BODY-MASS INDEX; STIMULATING HORMONE; EUTHYROID SUBJECTS; INSULIN-RESISTANCE; SERUM TSH; FREE T4; POPULATION; PREVALENCE; LEPTIN; HEALTH